Distinct but connected avian influenza virus activities in wetlands and live poultry markets in Bangladesh, 2018–2019. Issue 4 (17th January 2022) - Turner, Jasmine C. M.; Barman, Subrata; Feeroz, Mohammed M.; Hasan, Md. Kamrul; Akhtar, Sharmin; Walker, David; Jeevan, Trushar; Mukherjee, Nabanita; El‐Shesheny, Rabeh; Seiler, Patrick; Franks, John; McKenzie, Pamela; et al.
Abstract: From April 2018 to October 2019, we continued active surveillance for influenza viruses in Bangladeshi live poultry markets (LPMs) and in Tanguar Haor, a wetland region of Bangladesh where domestic ducks have frequent contact with migratory birds. The predominant virus subtypes circulating in the LPMs were low pathogenic avian influenza (LPAI) H9N2 and clade 2.3.2.1a highly pathogenic avian influenza (HPAI) H5N1 viruses of the H5N1‐R1 genotype, like those found in previous years. Viruses of the H5N1‐R2 genotype, which were previously reported as co‐circulating with H5N1‐R1 genotype viruses in LPM, were not detected. In addition to H9N2 viruses, which were primarily found in chicken and quail, H2N2, H3N8 and H11N3 LPAI viruses were detected in LPMs, exclusively in ducks. Viruses in domestic ducks and/or wild birds in Tanguar Haor were more diverse, with H1N1, H4N6, H7N1, H7N3, H7N4, H7N6, H8N4, H10N3, H10N4 and H11N3 detected. Phylogenetic analyses of these LPAI viruses suggested that some were new to Bangladesh (H2N2, H7N6, H8N4, H10N3 and H10N4), likely introduced by migratory birds of the Central Asian flyway. Our results show a complex dynamic of viral evolution and diversity in Bangladesh based on factors such as host populations and geography. The LPM environment was characterised by maintenance of viruses with demonstrated zoonotic potential and H5N1 genotype turnover. The wetland environment was characterised by greater viral gene pool diversity but a lower overall influenza virus detection rate. The genetic similarity of H11N3 viruses in both environments demonstrates that LPM and wetlands are connected despite their having distinct influenza ecologies.